Selection and implementation of open source tool for project portfolio management - Marek, Jan; Chlapek, Dušan; Kučera, Jan; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2016)
Methods and ways of implementation of changes and innovations in companies through project management are in today's society very well established. There exists methodologies, techniques and tools for the management of individual projects. However in a role of project manager, I very often faced the fact that companies are performing the project portfolio management in very intuitive way. This in itself leads to failed and prematurely terminated projects, initiation of the wrong projects or realisation of correct projects, but at the wrong time. Very often I have also recognized, that there is lack of awareness of fact, that there are also Open Source applications that can help with the organization's portfolio. This thesis deals with the definition of requirements, search and selection of proper OSS application and subsequent implementation. In the first part of this thesis I prepare a theoretical framework about PPM, and on that basis then identify and verify a set of requirements for selection of right OSS PPM application. The next section of thesis describes searching for suitable applications from a variety of sources, assessment against the requirements and the final selection. In the last part the implementation project is drafted, which aims to serve other colleagues in project management as one of the possible implementation paths. The outputs are then continuously confronted with experts in matter of projects and project management in the field of IT in order to maximize symbiosis between theory and real life experiences. Virtually every project management methodology defines the collection of already-proven techniques, best practices or lessons learned from the previous similar implementations. The main contribution of this thesis I see in fact that it contains not only the design of the project implementation, but also describes a logical path, what leads to the result.
Therefore this thesis could be used as a base or discussed best practice, when a project of implementation of PPM application in place.
Vedoucí práce: Dušan Chlapek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2017
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2017
Způsob přístupu: Internet
Keywords: podniková informatika [obor dipl. práce]; diplomové práce; master's theses